Nurses' Perception on the Implementation of Nursing Care Documentation Using Electronic Medical Record: A Literature Review - Eka Handayani; Tutik Sri Hariyati (Jurnal Ilmiah Ilmu Keperawatan Indonesia, 2023)
Background: The global use of Electronic Medical Records in healthcare service organizations such as hospitals is currently undertaken as a measure to enhance efficiency and safety in healthcare provision. Despite considerable attention being given to this aspect, the benefits of this technology are often not fully realized. Objectives: This research aims to examine the concept of electronic medical records about nurses' perceptions of nursing care documentation, particularly in healthcare services. Methods: The design of this research utilizes a literature review approach by collecting several articles from selected databases, including ScienceDirect and PubMed, with articles published from 2016 to 2023. An article search was conducted by using the keywords "(Electronic medical record) OR (EMR) OR (e-Health Record) AND (perception) OR (Perceived)". The search for articles was limited by inclusion and exclusion criteria. Inclusion criteria for this study encompassed articles investigating electronic medical records, Electronic Health Record (EHR), or Electronic Medical Record (EMR) with a design of a Crossectional Study, while exclusion criteria included non-health service-related articles, abstracts, and books only, as well as letters to the editor. Results: EMR provides significant benefits in clinical practice and healthcare services. The majority of respondents view EMR as a highly advantageous technology in terms of patient data access, workflow efficiency, and the improvement of service quality. Conclusion: This research can be used as a foundation for further development and improvement in the implementation of EMR to enhance the quality of service and patient safety in clinical practice.